2013
DOI: 10.1124/mol.113.088393
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of the Antitumor Agent Dp44mT Occurs via a Carrier/Receptor-Mediated Mechanism

Abstract: The chelator di-2-pyridylketone 4,4-dimethyl-3-thiosemicarbazone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 56 publications
(67 reference statements)
5
25
0
Order By: Relevance
“…These conditions have been previously demonstrated to efficiently induce iron depletion and increase the expression of iron-regulated molecules (Richardson et al, 1994;Yuan et al, 2004;Kovacevic et al, 2011). Furthermore, we have shown that Dp44mT uptake by cells saturates at 5-10 mM (Merlot et al, 2013b). At this concentration, the level of agent is pharmacologically relevant in humans, as the structurally related thiosemicarbazone Triapine has been observed in the serum at similar levels (Wadler et al, 2004;Chao et al, 2012).…”
Section: Resultsmentioning
confidence: 61%
“…These conditions have been previously demonstrated to efficiently induce iron depletion and increase the expression of iron-regulated molecules (Richardson et al, 1994;Yuan et al, 2004;Kovacevic et al, 2011). Furthermore, we have shown that Dp44mT uptake by cells saturates at 5-10 mM (Merlot et al, 2013b). At this concentration, the level of agent is pharmacologically relevant in humans, as the structurally related thiosemicarbazone Triapine has been observed in the serum at similar levels (Wadler et al, 2004;Chao et al, 2012).…”
Section: Resultsmentioning
confidence: 61%
“…However, studies have also demonstrated mechanisms by which albumin acts to effectively improve therapeutic use or reduce rapid clearance (Dennis et al, 2002; Merlot and Richardson, 2014). For instance, the experimental anti-cancer thiosemicarbazone, namely di-2-pyridylketone 4,4-dimethyl-3-thiosemicarbazone (Dp44mT) (Merlot et al, 2013a), has been shown to be internalized by cancer cells via a putative carrier/receptor (Merlot et al, 2013b; Merlot and Richardson, 2014). Interestingly, the uptake, toxicity and apoptotic activity of Dp44mT is greatly enhanced in the presence of HSA (Merlot and Richardson, 2014).…”
Section: Albumin As a Drug Carrier In Oncologymentioning
confidence: 99%
“…Interestingly, it has been recently demonstrated that Dp44mT binds to a saturable receptor/carrier on a variety of cell-types [ 34 ]. Other structurally-related thiosemicarbazones, such as 2-benzoylpyridine 4-ethyl-3-thiosemicarbazone (Bp4eT; Fig.…”
Section: Introductionmentioning
confidence: 99%